2015
DOI: 10.1016/j.sbspro.2015.02.055
|View full text |Cite
|
Sign up to set email alerts
|

A Contrastive Analysis of Metadiscourse Features in Business e-mails Written by Non-native Speakers of English

Abstract: Metadiscourse is usually studied in terms of a cross-cultural exploration of interpersonality, mainly in academic English, but we believe that this approach could be applied to other genres. The main purpose of this study is to compare some metadiscourse features used in digital business communications. More specifically, we focus on the interactional metadiscourse devices categorised as boosters. We analysed and compared a corpus of one hundred emails written by two groups of non-native speakers of English wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Text-based studies of metadiscourse in business texts have been confined to academic research articles (Cao & Hu, 2014;Dueñas, 2007Dueñas, , 2010Hyland, 2005c;Hyland & Tse, 2005a, 2005bKhedri, Heng, & Ebrahimi, 2013;Murillo, 2012;Pooresfahani, Khajavy, & Vahidnia, 2012;Sultan, 2011), master's theses and dissertations (Hyland, 2004;Samraj, 2008), and workplace contexts (Bargiela-Chiappini, 2009;Camiciottoli, 2010Camiciottoli, , 2011Carrió-Pastor & Calderón, 2015;Hyland, 1998a). Cao and Hu (2014) compared the use of interactive metadiscourse markers in 120 quantitative and qualitative research articles across three social science subfields: applied linguistics, education, and psychology.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Text-based studies of metadiscourse in business texts have been confined to academic research articles (Cao & Hu, 2014;Dueñas, 2007Dueñas, , 2010Hyland, 2005c;Hyland & Tse, 2005a, 2005bKhedri, Heng, & Ebrahimi, 2013;Murillo, 2012;Pooresfahani, Khajavy, & Vahidnia, 2012;Sultan, 2011), master's theses and dissertations (Hyland, 2004;Samraj, 2008), and workplace contexts (Bargiela-Chiappini, 2009;Camiciottoli, 2010Camiciottoli, , 2011Carrió-Pastor & Calderón, 2015;Hyland, 1998a). Cao and Hu (2014) compared the use of interactive metadiscourse markers in 120 quantitative and qualitative research articles across three social science subfields: applied linguistics, education, and psychology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings showed that the executives strongly focused on trustworthiness and commitment to moving forward by employing a variety of ethics-related terms. Carrió-Pastor and Calderón (2015) compared the use of boosters in a corpus of 100 emails written in English by Spanish and Chinese groups working in an export company. The findings showed that although some boosters (know, confirm) were used more frequently by the two groups, there was a cultural variation in the use of these devices: Spanish writers of English showed a preference for greater assertiveness (must) when communicating in business English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This phenomenon can be seen, for example, in the utilisation of certain expressions which are not found in 'standard English', in the different ways in which certain words are used, and in variations in language patterns. This aspect has been pointed out by several researchers, such as Yli-Jokipii and Jorgensen (2006), Carrió-Pastor (2009, 2014, 2019a, 2019b, Schleef (2009), Carrió-Pastor and Muñiz (2012, Candel and Carrió-Pastor (2013) and Carrió-Pastor and Candel (2013).…”
Section: Introductionmentioning
confidence: 80%
“…Dada la importancia de los lectores/interlocutores en este tipo de comunicación, creemos que es importante analizar los marcadores de compromiso que se utilizan para marcar el territorio del escritor y llamar la atención del lector. En líneas generales, los estudios sobre el metadiscurso se han centrado, principalmente, en el análisis del discurso académico (Hyland y Tse, 2004;Hyland, 2005a;Mur-Dueñas, 2011;Li y Wharton, 2012;Alonso Almeida y Carrió-Pastor, 2015;Carrió-Pastor, 2016), aunque algunos investigadores también los han utilizado para estudiar otros géneros discursivos (Carrió- Pastor y Muñiz Calderón, 2013, 2015a, 2015bGonzález Arias, 2014). En este artículo hemos decidido centrarnos en el estudio de los marcadores de compromiso, ya que este tipo de estrategias son vitales para lograr que se lean los comentarios a noticias y se repliquen.…”
Section: Los Comentarios En La Prensa Digital Y Los Marcadores De Comunclassified